Potentiation of plant defense by bacterial outer membrane vesicles is mediated by membrane nanodomains - Tran, Tuan Minh (2022)
Outer membrane vesicles (OMVs) are released from the outer membranes of Gram-negative bacteria during infection and modulate host immunity during host-pathogen interactions. The mechanisms by which OMVs are perceived by plants and affect host immunity are unclear. Here, we used the pathogen Xanthomonas campestris pv. campestris to demonstrate that OMV-plant interactions at the Arabidopsis thaliana plasma membrane (PM) modulate various host processes, including endocytosis, innate immune responses, and suppression of pathogenesis by phytobacteria. The lipid phase of OMVs is highly ordered and OMVs directly insert into the Arabidopsis PM, thereby enhancing the plant PM's lipid order; this also resulted in strengthened plant defenses. Strikingly, the integration of OMVs into the plant PM is host nanodomain- and remorin-dependent. Using coarse-grained simulations of molecular dynamics, we demonstrated that OMV integration into the plant PM depends on the membrane lipid order. Our computational simulations further showed that the saturation level of the OMV lipids could fine-tune the enhancement of host lipid order. Our work unraveled the mechanisms underlying the ability of OMVs produced by a plant pathogen to insert into the host PM, alter host membrane properties, and modulate plant immune responses.